Cephalopod ontogeny and life cycle patterns - Vidal, Erica A. G.; Shea, Elizabeth K. (Frontiers in Marine Science, 2023)
Life cycle definitions provide the background for conceptualizing meaningful questions to address the mechanisms that generate different life cycle patterns. This review provides explicit definitions and explanations of the steps in a cephalopod life cycle, from fertilization to death. Each large step, or phase, is characterized by a particular developmental process and morphology. Each phase is composed of smaller developmentally distinct steps, or stages. The cephalopod life cycle is comprised of all or some of the following phases: Embryonic, Paralarval, Juvenile, Subadult, Adult and Senescent, and each life cycle is taxon-specific. All cephalopods have direct development and maintain a consistent body plan throughout ontogeny (i.e., no true larval phase and no metamorphosis). Most cephalopods have a life cycle marked by a long early life and a short adult life followed by senescence. Cephalopods have two developmental modes: they produce either small planktonic hatchlings as paralarvae, or large hatchlings as juveniles. All cephalopods go through a Hatchling stage soon after eclosion during which they rely on two modes of nutrition: endogenous (yolk) and exogenous (prey). Many cephalopods with planktonic paralarvae will become benthic early in their life cycle during their Settlement stage or remain pelagic during their Metapelagic stage. Juvenile growth is fast and ontogenetic changes (outside of gonadal maturation) generally cease at the end of the Juvenile phase. The Subadult phase begins when the definitive adult morphology (except for size and body proportions) is acquired (e.g., full complement of photophores). Sexual organs undergo most of their development during the Subadult phase. The Adult phase starts with spawning competency and concludes when gonads are spent. The Senescent phase begins with spent gonads and ends with death. Using this new terminology, we examine the patterns of cephalopod life cycles and find that there are four main patterns based on the presence of a Paralarval phase and the habitat occupied by each phase: Holopelagic (all phases are pelagic), Holobenthic (all phases are benthic), Merobenthic and Meropelagic (phases alternate between benthic and pelagic environments). In these two last patterns, the main difference is the presence of a Paralarval phase in Merobenthic species. The definitions and terminology proposed here provide a unifying framework for future ecological, evolutionary and life cycles research on cephalopods.